The Effect of Good Corporate Governance Implementation on Islamic Bank Financial Performance - Rosada, Amrina (Universitas Negeri Semarang, 2021)
This study aims to examine the effect of Good Corporate Governance on Financial Performance at Islamic Banks. The independent variable in this study is Good Corporate Governance as measured by the board of directors, the independent board of commissioners, the islamic supervisory board and the audit committee. The population in this study were 11 Islamic commercial banks listed on the Indonesia Stock Exchange. This research data was obtained from the annual report for 2015-2019. The results showed that the audit committee has an effect on financial performance as measured by return on assets, while the board of directors, independent commissioners, and islamic supervisory board has no effect on financial performance as measured by return on assets. Together the board of directors, independent commissioners, islamic supervisory board and audit committee have an effect on return on asset.